2022
DOI: 10.1007/s44192-022-00012-3
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine treatment for depression: a review

Abstract: This manuscript reviews the clinical evidence regarding single-dose intravenous (IV) administration of the novel glutamatergic modulator racemic (R,S)-ketamine (hereafter referred to as ketamine) as well as its S-enantiomer, intranasal esketamine, for the treatment of major depressive disorder (MDD). Initial studies found that a single subanesthetic-dose IV ketamine infusion rapidly (within one day) improved depressive symptoms in individuals with MDD and bipolar depression, with antidepressant effects lasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 87 publications
1
35
0
6
Order By: Relevance
“…Recently, ketamine, a glutamate modulator, has attracted great attention due to its rapid antidepressant effect in adults ( Frizzo, 2019 ). Ketamine also appears to be effective in reducing anhedonia and suicidality in adolescent MDD patients, making ketamine a potentially valuable new treatment option for adolescents ( Dwyer et al, 2021 ; Yavi et al, 2022 ). An increase in BDNF mRNA or protein levels in the hippocampus and prefrontal cortex by ketamine treatment has been reported in animal models of depression ( Autry et al, 2011 ), and results from clinical studies of an increase in serum BDNF with ketamine treatment have also been reported in MDD patients ( Strasburger et al, 2017 ; Arosio et al, 2021 ).…”
Section: Brain-derived Neurotrophic Factor In the Treatment Of Adoles...mentioning
confidence: 99%
“…Recently, ketamine, a glutamate modulator, has attracted great attention due to its rapid antidepressant effect in adults ( Frizzo, 2019 ). Ketamine also appears to be effective in reducing anhedonia and suicidality in adolescent MDD patients, making ketamine a potentially valuable new treatment option for adolescents ( Dwyer et al, 2021 ; Yavi et al, 2022 ). An increase in BDNF mRNA or protein levels in the hippocampus and prefrontal cortex by ketamine treatment has been reported in animal models of depression ( Autry et al, 2011 ), and results from clinical studies of an increase in serum BDNF with ketamine treatment have also been reported in MDD patients ( Strasburger et al, 2017 ; Arosio et al, 2021 ).…”
Section: Brain-derived Neurotrophic Factor In the Treatment Of Adoles...mentioning
confidence: 99%
“…The informed consent procedure included extensive discussion of potential risks of ketamine, including sedation, headache, nausea, elevated blood pressure and heart rate, and perceptual disturbances. 27 While this study involved only a single dose, caregivers were also informed that repeated ketamine use has been associated with structural and functional brain changes, 28 cognitive problems, and increased inflammatory cytokines. 29 Ten participants were screened, and all met criteria for inclusion and were enrolled between August 2020 and May 2021.…”
Section: Methodsmentioning
confidence: 99%
“…The U.S. FDA approved the intranasal S-enantiomer of ketamine (Esketamine) in 2019 for the treatment of MDD in adults. The S-enantiomer of ketamine is more potent on NMDAR than the R-enantiomer and racemic ketamine [ 127 , 128 ]. R-enantiomer of ketamine exhibits more potent and longer-lasting antidepressant effects [ 129 ].…”
Section: Intranasal Administration Of Antidepressant Active Ingredientsmentioning
confidence: 99%